Grandfather Clause as Investor Protection in Bilateral Investment Treaties (Case Study: Oleovest PTE LTD Vs Indonesia) - Yonathan Manalu, Febri (SEAN Institute, 2025)
Bilateral Investment Treaties (BITs) aim to provide protection for investments made abroad, encourage policies that support free markets, and create transparent and non-discriminatory investment practices between countries and investors. This study aims to examine several important aspects related to BITs: first, to examine how the Grandfather Clause is applied in foreign investment. Second, to examine how BIT agreements are used to increase foreign investment. Third, to explore how the Grandfather Clause is applied as protection for foreign investors in BIT agreements, using the case study of Oleovest Pte Ltd vs Indonesia as a concrete example. The research method used is a normative approach based on an analysis of relevant laws and regulations. The results of the study show that: first, the application of the Grandfather Clause is important to ensure legal certainty and protection for foreign investors so that changes in policies related to investment in Indonesia do not affect approved investments. Second, BIT agreements focus on two main objectives, namely providing direct protection against risks and cooperating with other instruments to minimise risks in order to achieve the ultimate goal of increasing foreign investment. Third, the application of the Grandfather Clause in BIT agreements in this case can guarantee the rights and provide protection for foreign investors, as evidenced by the ICSID's acceptance of the claim in the Oleovest Pte Ltd vs Indonesia case.